A INFLUÊNCIA DA TECNOLOGIA NO ACESSO À JUSTIÇA (REMUNOM, 2024)
This article aims to discuss technology and its influence on access to justice. Using the observational method and the literature review procedure, an analysis is made of the development of the judicial process as a whole, at a global and national level. Brief considerations are made on the evolution of technology and its correlation with the principle of efficiency. The data treated here are the result of a survey that evaluated the use of technology in procedural practices within the scope of justice, in order to verify whether technological instruments enable procedural efficiency.Keywords: Separadas por ponto e vírgula.